Multiswitchable photoacid–hydroxyflavylium–polyelectrolyte nano-assemblies - Zika, Alexander; Gröhn, Franziska (Beilstein Journal of Organic Chemistry, 2021)
Light- and pH-responsive nano-assemblies with switchable size and structure are formed by the association of a photoacid, anthocyanidin, and a linear polyelectrolyte in aqueous solution. Specifically, anionic disulfonated naphthol derivatives, neutral hydroxyflavylium, and cationic poly(allylamine) are used as building blocks for the ternary electrostatic self-assembly, forming well-defined supramolecular assemblies with tunable sizes of 50 to 500 nm. Due to the network of possible chemical reactions for the anthocyanidin and the excited-state dissociation of the photoacid upon irradiation, different ways to alter the ternary system through external triggering are accessible. The structure and trigger effects can be controlled through the component ratios of the samples. Dynamic and static light scattering (DLS, SLS) and ζ-potential measurements were applied to study the size and the stability of the particles, and information on the molecular structure was gained by UV–vis spectroscopy. Isothermal titration calorimetry (ITC) provided information on the thermodynamics and interaction forces in the supramolecular assembly formation.
Keywords: electrostatic self-assembly; hydroxyflavylium; multiswitchable; photoacid; polyelectrolyte

(untitled) - Fenske, T.; Korth, H.-G.; Mohr, A.; Schmuck, C. (Chem. – Eur. J., 2012)

(untitled) - Krieg, E.; Bastings, M. M. C.; Besenius, P.; Rybtchinski, B. (Chem. Rev., 2016)

(untitled) - Konstantatos, G.; Howard, I.; Fischer, A.; Hoogland, S.; Clifford, J.; Klem, E.; Levina, L.; Sargent, E. H. (Nature, 2006)

(untitled) - Willerich, I.; Gröhn, F. (Angew. Chem., Int. Ed., 2010)

(untitled) - Crossland, E. J. W.; Noel, N.; Sivaram, V.; Leijtens, T.; Alexander-Webber, J. A.; Snaith, H. J. (Nature, 2013)

(untitled) - Tian, J.; Cheng, N.; Liu, Q.; Xing, W.; Sun, X. (Angew. Chem., Int. Ed., 2015)

(untitled) - Liu, K.; Xing, R.; Zou, Q.; Ma, G.; Möhwald, H.; Yan, X. (Angew. Chem., Int. Ed., 2016)

(untitled) - Wani, O. M.; Zeng, H.; Priimagi, A. (Nat. Commun., 2017)

(untitled) - Schmuck, C.; Wienand, W. (Angew. Chem., Int. Ed., 2001)

(untitled) - Goujon, A.; Du, G.; Moulin, E.; Fuks, G.; Maaloum, M.; Buhler, E.; Giuseppone, N. (Angew. Chem., Int. Ed., 2016)

(untitled) - Herbst, S.; Soberats, B.; Leowanawat, P.; Stolte, M.; Lehmann, M.; Würthner, F. (Nat. Commun., 2018)

(untitled) - Wasio, N. A.; Quardokus, R. C.; Forrest, R. P.; Lent, C. S.; Corcelli, S. A.; Christie, J. A.; Henderson, K. W.; Kandel, S. A. (Nature, 2014)

(untitled) - Percec, V.; Won, B. C.; Peterca, M.; Heiney, P. A. (J. Am. Chem. Soc., 2007)

(untitled) - Feng, X.; Pisula, W.; Kudernac, T.; Wu, D.; Zhi, L.; De Feyter, S.; Müllen, K. (J. Am. Chem. Soc., 2009)

(untitled) - Besenius, P.; Portale, G.; Bomans, P. H. H.; Janssen, H. M.; Palmans, A. R. A.; Meijer, E. W. (Proc. Natl. Acad. Sci. U. S. A., 2010)

(untitled) - Kaeser, A.; Schenning, A. P. H. J. (Adv. Mater. (Weinheim, Ger.), 2010)

(untitled) - Samanta, K.; Ehlers, M.; Schmuck, C. (Chem. – Eur. J., 2016)

(untitled) - Mishra, A. K.; Weissman, H.; Krieg, E.; Votaw, K. A.; McCullagh, M.; Rybtchinski, B.; Lewis, F. D. (Chem. – Eur. J., 2017)

(untitled) - Qiu, H.; Hudson, Z. M.; Winnik, M. A.; Manners, I. (Science, 2015)

(untitled) - Shao, H.; Seifert, J.; Romano, N. C.; Gao, M.; Helmus, J. J.; Jaroniec, C. P.; Modarelli, D. A.; Parquette, J. R. (Angew. Chem., Int. Ed., 2010)

(untitled) - Ahlers, P.; Götz, C.; Riebe, S.; Zirbes, M.; Jochem, M.; Spitzer, D.; Voskuhl, J.; Basché, T.; Besenius, P. (Polym. Chem., 2019)

(untitled) - Schmuck, C.; Wienand, W. (J. Am. Chem. Soc., 2003)

(untitled) - Schmuck, C.; Rehm, T.; Gröhn, F.; Klein, K.; Reinhold, F. (J. Am. Chem. Soc., 2006)

(untitled) - Schmuck, C.; Rehm, T.; Klein, K.; Gröhn, F. (Angew. Chem., Int. Ed., 2007)

(untitled) - Giese, M.; Niemeyer, J.; Voskuhl, J. (ChemPlusChem, 2020)

(untitled) - Rädler, J. O.; Koltover, I.; Salditt, T.; Safinya, C. R. (Science, 1997)

(untitled) - Faul, C. F. J.; Antonietti, M. (Adv. Mater. (Weinheim, Ger.), 2003)

(untitled) - Gröhn, F.; Klein, K.; Brand, S. (Chem. – Eur. J., 2008)

(untitled) - Willerich, I.; Gröhn, F. (Chem. – Eur. J., 2008)

(untitled) - Gröhn, F. (Soft Matter, 2010)

(untitled) - Mariani, G.; Moldenhauer, D.; Schweins, R.; Gröhn, F. (J. Am. Chem. Soc., 2016)

(untitled) - Kutz, A.; Mariani, G.; Schweins, R.; Streb, C.; Gröhn, F. (Nanoscale, 2018)

(untitled) - Carl, N.; Müller, W.; Schweins, R.; Huber, K. (Langmuir, 2020)

(untitled) - Ruthard, C.; Maskos, M.; Kolb, U.; Gröhn, F. (Macromolecules, 2009)

(untitled) - Willerich, I.; Ritter, H.; Gröhn, F. (J. Phys. Chem. B, 2009)

(untitled) - Gröhn, F.; Klein, K.; Koynov, K. (Macromol. Rapid Commun., 2010)

(untitled) - Willerich, I.; Gröhn, F. (J. Am. Chem. Soc., 2011)

(untitled) - Frühbeißer, S.; Gröhn, F. (J. Am. Chem. Soc., 2012)

(untitled) - Düring, J.; Hölzer, A.; Kolb, U.; Branscheid, R.; Gröhn, F. (Angew. Chem., Int. Ed., 2013)

(untitled) - Krieger, A.; Werner, J. P. F.; Mariani, G.; Gröhn, F. (Macromolecules, 2017)

(untitled) - Externbrink, M.; Riebe, S.; Schmuck, C.; Voskuhl, J. (Soft Matter, 2018)

(untitled) - Li, Y.; Song, L.; Wang, B.; He, J.; Li, Y.; Deng, Z.; Mao, C. (Angew. Chem., 2018)

(untitled) - Otter, R.; Klinker, K.; Spitzer, D.; Schinnerer, M.; Barz, M.; Besenius, P. (Chem. Commun., 2018)

(untitled) - Beck, J. B.; Rowan, S. J. (J. Am. Chem. Soc., 2003)

(untitled) - Li, X.; Kim, C.-y.; Lee, S.; Lee, D.; Chung, H.-M.; Kim, G.; Heo, S.-H.; Kim, C.; Hong, K.-S.; Yoon, J. (J. Am. Chem. Soc., 2017)

(untitled) - Moldenhauer, D.; Gröhn, F. (Chem. – Eur. J., 2017)

(untitled) - Cheng, Y.; Dong, J.; Li, X. (Langmuir, 2018)

(untitled) - Niehues, M.; Tegeder, P.; Ravoo, B. J. (Beilstein J. Org. Chem., 2019)

(untitled) - Davidson-Rozenfeld, G.; Stricker, L.; Simke, J.; Fadeev, M.; Vázquez-González, M.; Ravoo, B. J.; Willner, I. (Polym. Chem., 2019)

(untitled) - Jiang, H.; Jiang, Y.; Han, J.; Zhang, L.; Liu, M. (Angew. Chem., Int. Ed., 2019)

(untitled) - Kim, H.; Jeong, S.-M.; Park, J.-W. (J. Am. Chem. Soc., 2011)

(untitled) - Kahlfuss, C.; Métay, E.; Duclos, M.-C.; Lemaire, M.; Milet, A.; Saint-Aman, E.; Bucher, C. (Chem. – Eur. J., 2015)

(untitled) - Lewandowski, W.; Fruhnert, M.; Mieczkowski, J.; Rockstuhl, C.; Górecka, E. (Nat. Commun., 2015)

(untitled) - Xie, F.; Qin, L.; Liu, M. (Chem. Commun., 2016)

(untitled) - Zhou, Q.; Zhang, B.; Han, D.; Chen, R.; Qiu, F.; Wu, J.; Jiang, H. (Chem. Commun., 2015)

(untitled) - He, H.; Feng, M.; Chen, Q.; Zhang, X.; Zhan, H. (Angew. Chem., Int. Ed., 2016)

(untitled) - Guan, S.; Chen, A. (ACS Macro Lett., 2020)

(untitled) - Li, S.; Moosa, B. A.; Croissant, J. G.; Khashab, N. M. (Angew. Chem., 2015)

(untitled) - Zhou, H.; Lu, Y.; Qiu, H.; Guerin, G.; Manners, I.; Winnik, M. A. (Macromolecules, 2015)

(untitled) - Willerich, I.; Gröhn, F. (Macromolecules, 2011)

(untitled) - Wang, Y.; Xu, J.-F.; Chen, Y.-Z.; Niu, L.-Y.; Wu, L.-Z.; Tung, C.-H.; Yang, Q.-Z. (Chem. Commun., 2014)

(untitled) - Song, H.; Jing, C.; Ma, W.; Xie, T.; Long, Y.-T. (Chem. Commun., 2016)

(untitled) - Xing, P.; Chen, H.; Ma, M.; Xu, X.; Hao, A.; Zhao, Y. (Nanoscale, 2016)

(untitled) - Zhu, H.; Shangguan, L.; Xia, D.; Mondal, J. H.; Shi, B. (Nanoscale, 2017)

(untitled) - Mariani, G.; Krieger, A.; Moldenhauer, D.; Schweins, R.; Gröhn, F. (Macromol. Rapid Commun., 2018)

(untitled) - Cardenas-Daw, C.; Gröhn, F. (J. Am. Chem. Soc., 2015)

(untitled) - Zika, A.; Bernhardt, S.; Gröhn, F. (Polymers (Basel, Switz.), 2020)

(untitled) - Callahan, D. J.; Liu, W.; Li, X.; Dreher, M. R.; Hassouneh, W.; Kim, M.; Marszalek, P.; Chilkoti, A. (Nano Lett., 2012)

(untitled) - Stoffelen, C.; Voskuhl, J.; Jonkheijm, P.; Huskens, J. (Angew. Chem., Int. Ed., 2014)

(untitled) - Chi, X.; Ji, X.; Xia, D.; Huang, F. (J. Am. Chem. Soc., 2015)

(untitled) - Chen, S.; Jiang, F.; Cao, Z.; Wang, G.; Dang, Z.-M. (Chem. Commun., 2015)

(untitled) - Hu, X.-Y.; Jia, K.; Cao, Y.; Li, Y.; Qin, S.; Zhou, F.; Lin, C.; Zhang, D.; Wang, L. (Chem. – Eur. J., 2015)

(untitled) - He, H.; Ostwaldt, J.-E.; Hirschhäuser, C.; Schmuck, C.; Niemeyer, J. (Small, 2020)

(untitled) - Pina, F.; Melo, M. J.; Maestri, M.; Ballardini, R.; Balzani, V. (J. Am. Chem. Soc., 1997)

(untitled) - Pina, F.; Lima, J. C.; Parola, A. J.; Afonso, C. A. M. (Angew. Chem., Int. Ed., 2004)

(untitled) - Petrov, V.; Slavcheva, S.; Stanimirov, S.; Pina, F. (J. Phys. Chem. A, 2015)

(untitled) - Pina, F.; Melo, M. J.; Laia, C. A. T.; Parola, A. J.; Lima, J. C. (Chem. Soc. Rev., 2012)

Molecular Switches - Feringa, B. L.; Browne, W. R. (Wiley-VCH, 2011)

(untitled) - Costa, D.; Galvão, A. M.; Di Paolo, R. E.; Freitas, A. A.; Lima, J. C.; Quina, F. H.; Maçanita, A. L. (Tetrahedron, 2015)

(untitled) - Basílio, N.; Pina, F. (Molecules, 2016)

(untitled) - Choi, J.; Rubner, M. F. (Macromolecules, 2005)

(untitled) - Prémont-Schwarz, M.; Barak, T.; Pines, D.; Nibbering, E. T. J.; Pines, E. (J. Phys. Chem. B, 2013)

(untitled) - Gröhn, F. (Macromol. Chem. Phys., 2008)

(untitled) - Kutz, A.; Alex, W.; Krieger, A.; Gröhn, F. (Macromol. Rapid Commun., 2017)

(untitled) - Shi, L.; Fleming, C. J.; Riechers, S. L.; Yin, N.-N.; Luo, J.; Lam, K. S.; Liu, G.-y. (J. Drug Delivery, 2011)

(untitled) - Willerich, I.; Li, Y.; Gröhn, F. (J. Phys. Chem. B, 2010)

(untitled) - Moldenhauer, D.; Gröhn, F. (J. Polym. Sci., Part B: Polym. Phys., 2013)

(untitled) - Spencer, J. N.; Wolbach, W. S.; Hovick, J. W.; Ansel, L.; Modarress, K. J. (J. Solution Chem., 1985)

(untitled) - Meot-Ner, M. (Chem. Rev., 2005)

(untitled) - Späth, A.; König, B. (Beilstein J. Org. Chem., 2010)

(untitled) - Farah, L.; Giles, G.; Wilson, D.; Ohno, A.; Scott, R. M. (J. Phys. Chem., 1979)

(untitled) - Valotteau, C.; Sumbul, F.; Rico, F. (Biophys. Rev., 2019)

(untitled) - Gołek, F.; Mazur, P.; Ryszka, Z.; Zuber, S. (Appl. Surf. Sci., 2014)

Atomic Force Microscopy. Methods in Molecular Biology - Ricci, D.; Braga, P. C. (Recognizing and avoiding artifacts in AFM imaging, 2004)